BUREAUCRATIC REFORM: CORRUPTION IN INDONESIA’S BUREAUCRACY - Sitohang, Irma Natasya (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2023)
Bureaucratic Reform of the Government of Indonesia in Grand Design Bureaucratic Reform is expected to become a World Class Bureaucracy with a bureaucratic reform agenda that has started since 2010 and will end in 2024. This research is research based on secondary data that utilizes various data and documents from various sources in the form of reports , research, books, journals and other data from the government and private parties that are captured through Harzing's Publish or Perish on Google Scholar and the government's official website. This study uses 2 main indicators, namely the Development of Corruption in the Indonesian Government Bureaucracy, and Bureaucratic Reform Efforts. The results of the study show that criminal acts of corruption are still high in the Indonesian government bureaucracy even though efforts to reform the Indonesian government bureaucracy have been carried out and are currently better, but at the regional government level it still needs to be a major concern because in addition to the high level of corruption, the index of bureaucratic reform in local government still quite low.